The pearl thief - Wein, Elizabeth (Hyperion, 2017)
Fifteen-year-old Julia Beaufort-Stuart wakes up in a hospital not knowing how she was injured, and soon befriends Euan McEwen, the Scottish Traveller boy who found her, and later, when a body is discovered, she experiences the prejudices his family has endured and tries to keep them from being framed for the crime.